1999
DOI: 10.3354/dao038001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and PCR detection of hepatopancreatic parvovirus (HPV) from Penaeus monodon in Thailand

Abstract: Hepatopancreatic parvovirus (HPV) causes disease in several species of penaeid shrimp. Heavy infections may result in poor growth and reduced production for shrimp farmers. From one southern Thai shrimp pond with a high prevalence of HPV infection, 790 shrimp were sampled randomly and the hepatopancreas (HP) removed. Most HP were preserved in liquid nitrogen. However, every 10th HP (79 total) was divided into 2 parts appropriately fixed for examination by transmission electron microscopy (TEM) and light micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…The economic impact of high HPV infection, such as that recorded in our samples, has not been established. It was initially suggested that the percentage of HPVinfected larvae prior to pond stocking would approximately correspond to the expected minimum mortality for that pond based on the experiences of Thai shrimp farmers (Sukhumsirichart et al 1999). This means that an infection rate of 60% HPV in PL prior to stocking would result in roughly 60% mortality in culture ponds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The economic impact of high HPV infection, such as that recorded in our samples, has not been established. It was initially suggested that the percentage of HPVinfected larvae prior to pond stocking would approximately correspond to the expected minimum mortality for that pond based on the experiences of Thai shrimp farmers (Sukhumsirichart et al 1999). This means that an infection rate of 60% HPV in PL prior to stocking would result in roughly 60% mortality in culture ponds.…”
Section: Resultsmentioning
confidence: 99%
“…Harvest losses incurred from stunted shrimp can sometimes be considerable, since stunted shrimp are much less valuable than normal shrimp. Therefore, it is necessary to check also for HPV in PL prior to pond-stocking (Flegel et al 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other type has been identified Chaivisuthangkura P et al . Detection of shrimp viruses by immunoassays in infected P. monodon from Thailand and India [78,81] . The complete genome of PmDNV isolated from infected P. monodon in Thailand consists of 6321 nucleotides, representing three ORFs and two non-coding termini.…”
Section: Pmdnvmentioning
confidence: 99%
“…PmDNV is a non-enveloped icosahedral virus that is 22-23 nm in diameter and contains linear ssDNA. It belongs to the family Parvoviridae in the densovirus group [77,78] . Two Asian types of PmDNV have been characterized at the molecular level.…”
Section: Pmdnvmentioning
confidence: 99%